Influence of the average molar mass of poly(N-vinylpyrrolidone) on the dimensions and conductivity of silver nanowires. Issue 18 (22nd March 2019) - Sonntag, Luisa; Eichler, Franziska; Weiß, Nelli; Bormann, Ludwig; Ghosh, Dhriti S.; Sonntag, Jannick M.; Jordan, Rainer; Gaponik, Nikolai; Leo, Karl; Eychmüller, Alexander
Abstract : Improving the performance of Ag nanowire electrodes by adjusting the reaction conditions and the molar mass of PVP. Abstract : We investigate the influence of the average molar mass ( M w ) of the capping agent poly( N -vinylpyrrolidone) (PVP) on the conductivity of a silver nanowire (AgNW) network. During the polyol process, the chain length of PVP is known to influence the AgNW diameters and lengths. By altering the reaction temperature and time and using PVP of different chain lengths, we synthesized AgNWs with varying diameters, lengths and PVP coverage. The obtained plethora of AgNWs is the basis for conductivity investigations of networks made of AgNWs with a diameter of either 60 nm or 80 nm. The results show a negative influence of long-chain PVP on the conductivity of the subsequent network if 60 nm thick AgNWs are employed. Overall, we obtain well performing AgNW transparent electrodes on glass with R S = 24.4 Ω sq −1 at 85.5% T 550nm .